First application of low temperature thermochronology as a tool for geothermal exploration: A promising, preliminary test from the Larderello-Travale geothermal field (Italy). (January 2023) - Montanari, Domenico; Ruggieri, Giovanni; Bonini, Marco; Balestrieri, Maria Laura
Highlights: A review of ages of granite emplacement is reported Low temperature thermochronology as a new tool for geothermal exploration Apatite fission track data may reveal buried magmatic intrusions The Mid-Tuscany Metamorphic Ridge is a promising exploration target Abstract: High enthalpy geothermal fields are typically associated with magmatic intrusions providing the heat source that makes the system working. To identify and locate these features, geothermal exploration generally uses expensive, time-consuming approaches that could also require complex logistics. Here we present the result of a pilot study carried out in the well-known Larderello-Travale geothermal field (Tuscany, Italy), exploring the possibility of an advantageous use of low temperature thermochronology to obtain useful information implementing the geothermal exploration workflow. The majority of the collected samples (except one retaining the apatite fission-track age of undisturbed, or almost undisturbed country rocks) cluster in a close time span ranging between 3.1±0.8 and 1.9±1.1 Ma, which clearly matches the known ages of magmatic bodies in the region. We propose that this approach can contribute to the identification of sectors recently affected by thermal perturbations that could have led to the development of hydrothermal systems. This approach has allowed us to achieve clues for the presence of subsurface magmatic intrusions even in areas where currently there are no direct indications. Given the small number and distribution of analyzed samples, our contribution represents a first attempt that demonstrates the potentiality of the method in geothermal exploration, but that needs to be verified by further studies involving a larger sampling density. Overall, our results suggest how low temperature thermochronology can be a powerful, fast, and cost-effective tool for geothermal exploration, to be used jointly with the classical methods.